Ba-doped ZnO nanostructure: X-ray line analysis and optical properties in visible and low frequency infrared. Issue 11 (15th August 2016) - Zamiri, Reza; Mahmoudi Chenari, Hossein; Moafi, H.F.; Shabani, Mehdi; Salehizadeh, S.A.; Rebelo, Avito; Kumar, J. Suresh; Graça, M.P.F.; Soares, M.J.; Ferreira, J.M.F.
Abstract: In this work, X-ray diffraction analysis and optical properties of pure and Ba-doped ZnO nanoparticles prepared by the precipitation method were investigated. X-ray analysis was employed to evaluate the micro structural parameters of ZnO nanoparticles in terms of crystallite sizes and lattice strain by the Williamson–Hall method. The average crystallite size of Ba-doped ZnO nanoparticles estimated by the Williamson–Hall method varied as the doping concentration increased. The effect of Ba doping on the photoluminescence (PL) emission spectrum of ZnO was also investigated. The temperature dependence of the PL emissions was also studied, and it was found that at low temperature, the samples show stronger emissions than those at room temperature in both UV and visible regions. As a final point, the FT–IR reflection spectrum along with Kramers–Kronig (K–K) method and classical dispersion theory was applied to obtain optical properties of the samples at low frequency infrared regime.